Theoretical modeling and simulation of MEMS piezoelectric energy harvester - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin; Salleh, Hanim (2010)
Energy harvesting devices, capable of converting wasted ambient energy to electrical power are rapidly gaining popularity as a source of green and renewable energy. This work presents the design and simulation of MEMS based piezoelectric cantilever beam which can both harvest energy as well as monitor critical vibration frequencies in power plant gas turbines. The design of the energy harvesters consists of a cantilever beam structure with the interdigitated electrodes on the zinc oxide piezoelectric layer with nickel proof mass at the end of the beam. A mechanical finite element simulation was conducted using CoventorWare #x00A9;. This paper illustrates the proposed theoretical modeling and simulation of piezoelectric energy harvesters.